Intelligent system of paraconsistent logic to control autonomous moving robots - Torres, Claudio Rodrigo; Lambert-Torres, Germano; Borges da Silva, Luiz Eduardo; Abe, Jair Minoro [UNESP]; IEEE (Ieee, 2006)
This paper shows a controller based on the evidential annotated paraconsistent logic E - Paracontrol. The Paracontrol is a variation of the logic analyzer. This work also shows an autonomous mobile robot, which is named Emmy II, in order to demonstrate the Paracontrol's new properties. As an innovation, the Paracontrol presents besides the characteristics of the previous controller (manipulation of uncertainties, contradiction and paracompleteness information), the speed control in the various robot's actions.